2021
DOI: 10.1007/s00345-020-03576-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher than expected and significantly increasing incidence of upper tract urothelial carcinoma. A population based study

Abstract: Purpose To register all cases of urothelial cancer and renal cell carcinoma (RCC) in Norway during 1999–2018 to obtain the contemporary incidence of UTUC and UTUC incidence relative to other urothelial cancers and RCC. Further to analyse possible changes over time regarding UTUC incidence, UTUC patient characteristics, tumour characteristics and survival. Methods 3502 cases registered with ICD code C65 and C66 during 1999–2018 at the Norwegian cancer regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Two other population-based studies, one conducted in the UK and one in Denmark, describing the periods 1985-2009 and 1944-2003, respectively, also found an increase in UTUC incidence [20,21]. The most recent publication on trends in the incidence of UTUC was based on the Norwegian cancer registry, which reported a similar trend over time to that found in our study; an increase in incidence from 3.21 to 4.71 per 100 000 person-years during the period 1999 to 2018 [22].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Two other population-based studies, one conducted in the UK and one in Denmark, describing the periods 1985-2009 and 1944-2003, respectively, also found an increase in UTUC incidence [20,21]. The most recent publication on trends in the incidence of UTUC was based on the Norwegian cancer registry, which reported a similar trend over time to that found in our study; an increase in incidence from 3.21 to 4.71 per 100 000 person-years during the period 1999 to 2018 [22].…”
Section: Discussionsupporting
confidence: 86%
“…57% in both studies) in 830 UTUC patients between 1995 and 2004 [ 38 ]. Contrary, the 5‐year cancer‐specific survival in Norway improved between 1999 and 2018 from 57.4% to 65.4% [ 22 ]. Although information on adjuvant treatment regarding UTUC was limited, the authors stated that this improvement might be explained by the increased use of peri‐operative chemotherapy and the introduction of immunotherapy in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Seven corresponding authors were contacted for the raw data of graphs in their respective articles, to which four authors [15][16][17][18] replied with this data. In total, eight papers required data extraction using WebPlotDigitizer (Additional file 2).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 12 studies reported incidence of UTUC according to age [14,[17][18][19][20][21][22][23][24][25][26][27][28]. The measures used to report incidence varied widely between different studies.…”
Section: Incidence By Agementioning
confidence: 99%
“…UTUC is a rare and under‐recognized malignancy with an incidence range of 1.2–4.7 cases per 100 000 person‐years globally. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Although exposure to smoking, alcohol consumption, aromatic amines, arsenic, aristolochic acid and so on have been considered as factors highly associated with UTUC development, 10 identifying individuals with a high risk of UTUC is usually challenging. Smoking and alcohol consumption are usually related to other cancers, and the other specific exposures are quite difficult to assess.…”
Section: Introductionmentioning
confidence: 99%